X-Reality Museums: Unifying the Virtual and Real World Towards Realistic Virtual Museums - George Margetis; Konstantinos C. Apostolakis; Stavroula Ntoa; George Papagiannakis; Constantine Stephanidis (Applied Sciences, 2020)
Culture is a field that is currently entering a revolutionary phase, no longer being a privilege for the few, but expanding to new audiences who are urged to not only passively consume cultural heritage content, but actually participate and assimilate it on their own. In this context, museums have already embraced new technologies as part of their exhibitions, many of them featuring augmented or virtual reality artifacts. The presented work proposes the synthesis of augmented, virtual and mixed reality technologies to provide unified X-Reality experiences in realistic virtual museums, engaging visitors in an interactive and seamless fusion of physical and virtual worlds that will feature virtual agents exhibiting naturalistic behavior. Visitors will be able to interact with the virtual agents, as they would with real world counterparts. The envisioned approach is expected to not only provide refined experiences for museum visitors, but also achieve high quality entertainment combined with more effective knowledge acquisition.